Bilateral administration of autologous CD133+ cells in ambulatory patients with refractory critical limb ischemia: lessons learned from a pilot randomized, double-blind, placebo-controlled trial - Raval, Amish N.; Schmuck, Eric G.; Tefera, Girma; Leitzke, Cathlyn; Ark, Cassondra Vander; Hei, Derek; Centanni, John M.; de Silva, Ranil; Koch, Jill; Chappell, Richard G.; Hematti, Peiman (Cytotherapy (Oxford, England), 2014)
CD133+ cells confer angiogenic potential and may be beneficial for the treatment of critical limb ischemia (CLI). However, patient selection, blinding methods and end points for clinical trials are challenging. We hypothesized that bilateral intramuscular administration of cytokine-mobilized CD133+ cells in ambulatory patients with refractory CLI would be feasible and safe. In this double-blind, randomized sham-controlled trial, subjects received subcutaneous injections of granulocyte colony-stimulating factor (10 μg/kg per day) for 5 days, followed by leukapheresis, and intramuscular administration of 50–400 million sorted CD133+ cells delivered into both legs. Control subjects received normal saline injections, sham leukapheresis and intramuscular injection of placebo buffered solution. Subjects were followed for 1 year. An aliquot of CD133+ cells was collected from each subject to test for genes associated with cell senescence. Seventy subjects were screened, of whom 10 were eligible. Subject enrollment was suspended because of a high rate of mobilization failure in subjects randomly assigned to treatment. Of 10 subjects enrolled (7 randomly assigned to treatment, 3 randomly assigned to control), there were no differences in serious adverse events at 12 months, and blinding was preserved. There were non-significant trends toward improved amputation-free survival, 6-minute walk distance, walking impairment questionnaire and quality of life in subjects randomly assigned to treatment. Successful CD133+ mobilizers expressed fewer senescence-associated genes compared with poor mobilizers. Bilateral administration of autologous CD133+ cells in ambulatory CLI subjects was safe, and blinding was preserved. However, poor mobilization efficiency combined with high CD133+ senescence suggests futility in this approach.